ความสุขในการทำงานของพนักงานการไฟฟ้าฝ่ายผลิตแห่งประเทศไทยแม่เมาะ จังหวัดลำปาง - ขนิษฐา พันธุ์ทอง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2016)
The objective of this research is to study about working conditions, happiness of work including the problems which happened from work of Electricity Generating Authority of Thailand, Mae Moh District, Lampang Province. Sampling staffs of this study are to question 400 people consists of Mae Moh’s 160 Employees, and Mao Moh’s 240 staffs of Electricity Generating Authority. Data analysis was used described statistics. Happiness measurement was divided into four parts such as work economic, health, work welfare, and the work problems. Likert scale was used to analyze the data of happiness and the problems. The results of this study found that staffs of Mao Moh District mostly were male, average age 29 years old, graduated bachelors and up, married, Northern area, average income from 50,000 to 70,000 Baht. Personal diseases were hypercholesterolemia and blood pressure. Most of them did not take exercise, but smoked cigarettes and drank alcohols. Work shift of Electricity Generating Authority of Thailand, Mae Moh District was average 11-year experiences. They worked every day from Monday to Friday. Someone who had technical position 5-7 levels could use reflected waistcoat for security. Most of them were provided money welfare for helping children and delivering baby. They could get equal bonus. Work happiness was medium. Health was number one such as no personal diseases and illness from work. Next was working condition because there were good activities and relationship among colleagues including security tools for work. Sampling group had medium problem of work such as existing work was not suitable for qualification of study including low growing and progressing. Sampling group of Mao Moh’s electricity generating, most of staffs were male average 36 years old, graduated bachelor degree, married, Northern area, average salary from 10,000 to 30,000 Baht. They did not have personal diseases. They did not take exercise but smoked cigarettes. Working duration at Electricity Generating Authority of Thailand, Mao Moh District average nine years experiences which worked as shift. There was a position of engineer that 2-4 employees position levels and employees 5-7 levels. Sample group satisfied to work highly which number one was work because they were safe to work and receive trust of work. Next variable was health because food Consumption was enough five categories and no personal diseases. Sample group had problems of low level work such as low income including low growing and progressing.